Effectiveness of Supramaximal Angiotensin-converting Enzyme Inhibition in Controlling Proteinuria in Congenital Nephrotic Syndrome with Cytomegalovirus Infection and an NPHS1 Mutation - Nimisha Dange; Kiran P. Sathe; Alpana Kondekar; Vishal Sawant (Saudi Journal of Kidney Diseases and Transplantation, 2023)
Congenital nephrotic syndrome (NS) is characterized by early-onset heavy proteinuria. Most cases of congenital NS are associated with genetic mutations in the podocyte proteins. The causal relationship of perinatal infections with congenital NS has not yet been proven. Inadequate response to the treatment of such infections should prompt us to conduct genetic testing for congenital NS. The heavy proteinuria associated with congenital NS is usually difficult to control with conventional treatment. It often results in progressive kidney disease with a high risk of mortality in early life. Here, we describe an infant who developed congenital NS and was found to have a coexisting Cytomegalovirus infection and an underlying NPSH1 mutation. Proteinuria did not respond to a standard dose of enalapril. A supramaximal dose of enalapril was tried and was effective and safe in controlling the proteinuria. It was associated with improved growth, complete resolution of edema, normal serum albumin, and normal renal function beyond 2 years of age.